كتاب (محاولات في النقد) لمحمد محمد علي قراءة نقدية - علي الطيب, أبو صباح (قــــــراءات, 2019)
كتاب (محاولات في النقد) لمحمد محمد علي، من الكتب التي لها خطرها في حركة النقد الأدبي في السودان، فهو يضعنا في كنف ناقد متمكن، يصدر عن ثقافة واعية، ورؤية ثاقبة، وأسلوب ماتع. هدفت الدراسة إلى التعريف بقيمة الكتاب، الذي لم ينل منه تقادم السنوات، التي شهدت بداياته مقالات أدبية، ونقدية جريئة، وواثقة اتسمت بالجدة، والطرافة طرحها صاحبها على صفحات الصحافة السودانية في الفترة ما بين 1952- 1958م، في محاولة منه لإثبات صورة تعبر عن واقع الأدب السوداني في قوة، ووضوح، وبأسلوب يعنى بالفكرة في السياق الأدبي، ويعمل على مناقشتها، وفق ضوابط النقد العلمية، تسنده في ذلك ثقافته الواسعة، واعتداده بآرائه التي لا يعترف معها بغير الحقيقة، ولم يخضعها تهيب الأسماء الكبيرة في نقدنا العربي للصمت، أو المسايرة، فكان نقده أصيلاً في التعبير عما يؤمن به من أفكار. تحتوي الدراسة على مقدمة تعرف بالكتاب، وتعدد فصوله، وتبين منهج الناقد في مناقشة الأفكار، وتحليل النصوص، وتوازن بين الآراء المختلفة، لتخلص منها إلى نتيجة تشي بقيمة كتاب أصيل، يمثل منجزاً نقدياً ما تزال الآراء، والأفكار فيه تغري بالدرس، والتحليل، والمراجعة، وكأنها كتبت للتو. وتنتهي الدراسة إلى نتائج ترى في مواقف الناقد محمد محمد علي تراوحاً بين النقد، ونقد النقد، فضلاً عن حقيقة ماثلة يجليها كتابه، مفادها: أن النقد جهد إنساني من شأنه التأرجح بين القوة، والضعف، وإن تكن ثمة كلمة أخيرة، فتوصية بدراسات أخرى تكشف عن الفكر التجديدي الذي لا تخطئه العين ماثلاً في تضاعيف كتاب (محاولات في النقد)، وتخبر عنه مواقفه النقدية بعامة.   Abstract Endeavors in Criticism by Muhammad Muhammad Ali is a significant book in the literary criticism movement in the Sudan. It puts us with a talented, educated, and farsighted critic who is equipped with an appealing style. This paper aims at showing the value of the book which has long stood the years; its introduction includes daring literary and critical articles characterized with seriousness and wit which the writer presented in the Sudanese press in the years 1952-1958 AD. He tried to depict a realistic, efficient, clear, and transparent image of the Sudanese literature in a style that incorporates thought in a literary discourse that follows the standards of scientific criticism, powered by his extensive education and self confidence in his views that maintain truth. He has not been underpowered by the great critics in the Arabic literature. He had an original criticism of his own that expresses his ideas. The study incorporates an introduction of the book, variety of its chapters, the critic's methodology in explaining his views, text analysis, and consensus of various viewpoints, resulting in a valuable original book considered as a product in criticism whose ideas and views still attract people for further study, analysis, and revision as if they were written just now. The study ends with results that see Muhammad Muhammad's viewpoints a variety of criticism, criticism of criticism, in addition to the idea his book explores: criticism is a human effort that fluctuates from strength to weakness. Finally, a recommendation for further studies explores those modernist thoughts that are transparent in the book, Endeavors in Criticism , and foretell his viewpoints in literary criticism generally.